Models and algorithms for dynamic headway control. (January 2017) - Fu, Lunce; Dessouky, Maged
Highlights: A formulation is given for train routing and scheduling with dynamic headway. A proposed velocity and headway control heuristics are developed. Simulation results show that using dynamic headway can reduce delay for trains. Abstract: We consider the dynamic headway control problem under no-deadlock and no-collision constraints. Different speed limits are applied to different railway segments and junctions according to local geographic conditions. A mathematical programming formulation is given under the consideration of the trains' dynamics. Then a heuristic rule for train movement is proposed to reduce delay and guarantees a safety distance between trains. Simulation experiments are also conducted to show the efficiency of the dynamic headway model together with the proposed heuristics.